Failure of the Anticoagulant Therapy and Psychological Distress: Still Far From a Bridge - Galli, Federica; Borghi, Lidia; Faioni, Elena; Cavicchioli, Marco; Ferrari Losi, Jessica; Vegni, Elena (Frontiers in Psychology, 2018)
Background: The procoagulant stress response reflects part of a beneficial adaptation of the organism to environmental threats, but a protracted procoagulant state generates a thrombotic risk. Atrial fibrillation (AF) is the most common arrhythmia in the general population. Patients with AF have a higher risk of thromboembolic events and stroke, therefore they are treated with long-term oral anticoagulant (OAC) therapy. The aim of this study is to evaluate if there is any association between psychological distress and clinically unexplained variations of the International Normalized Ratio (INR), that is the index used to monitor both thromboembolic and bleeding risk in the case of patients under OAC therapy. Methods: Fifty-eight patients (men = 27; women = 31; mean age = 74.98) were recruited. The sample was divided according to the recognition (or not) of the reason why the INR was subtherapeutic (<2) and classified as “Known Reasons” (KR = 32.8%) and “Unknown Reasons” (UR = 67.2%). Psychological assessment included the following dimensions: symptoms of anxiety and depression, perceived stress, emotional regulation strategies, and alexithymia. Results: Considering Mann–Whitney test results, no significant difference was found in the scores of anxiety, depression, stress, and emotional regulation strategies. With regard to alexithymia, UR patients are characterized by a moderate tendency to an outward-oriented thinking (r = 0.25). Conclusion: A clear role for the detected psychological factors in determining abnormal INR range in patients under OAC therapy could not be found. Further studies are needed to support our findings, if possible exploring factors other than psychological distress and the related emotion regulation strategies.